Gênero e sexualidade sob a perspectiva de docentes de biologia da rede estadual do município de Aparecida de Goiânia - Sousa, Jéssica Cristtinny Oliveira de (2018)
The present dissertation aims to identify the social representations of gender and sexuality by Biology teachers of public education, working at High Schools in the city of Aparecida de Goiânia. The theory of social representations was applied as a theoretical methodology contribution, considering that it is based on knowledge arising from the experiences and actions of individuals and groups. Therefore, this theory leads on how to proceed under certain circumstances. The research methodology was the analysis of content from Laurence Bardin, employing the association of words technique. Material produced from 35 questionnaires and seven interviews, adding up to 42 participants divided into 29 schools were, consequently analyzed. According to available answers and reports, data for analysis was categorized and systematized. Based on the research and data analysis, we could identify that teachers do not have any particular training to discuss gender and sexuality in an educational environment. Moreover, they are not familiar with public policies that support them throughout this journey (in fact, these aspects are not discussed and are entirely omitted in the educational environment nowadays). The present situation reflects the power that political, religious and civil conservatism scenario has been taking place. The school, the curriculum, the guiding documents and the teachers become the target of powerful strategies applied to limit rights and shape the diversities of gender and sexuality among others, within a principle of universal and determined identity. Such orientations require a position of resistance, from the teaching practice to the outer movements and at the same time, the attitude of look to the Other, to deal with the diversity of identities that compose the school reality.